2020
DOI: 10.1609/aaai.v34i04.6172
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Maximum Likelihood and Adversarial Learning via α-Divergence

Abstract: Maximum likelihood (ML) and adversarial learning are two popular approaches for training generative models, and from many perspectives these techniques are complementary. ML learning encourages the capture of all data modes, and it is typically characterized by stable training. However, ML learning tends to distribute probability mass diffusely over the data space, e.g., yielding blurry synthetic images. Adversarial learning is well known to synthesize highly realistic natural images, despite practical challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Poor performance in certain aspects may be overshadowed by good performance elsewhere. This can result in cases where increased hold-out likelihoods do not correspond to better sample quality, as noted in the ML literature (Goodfellow et al, 2014;Grover et al, 2018;Theis et al, 2015;Zhao et al, 2020) and seen in our results: the RNN has a worse F = 28 hold-out likelihood than the polynomial, yet the polynomial model explodes unlike the RNN. In this case, the phenomenon of 'explosion' is not significantly penalising the likelihood.…”
Section: For Evaluationsupporting
confidence: 62%
“…Poor performance in certain aspects may be overshadowed by good performance elsewhere. This can result in cases where increased hold-out likelihoods do not correspond to better sample quality, as noted in the ML literature (Goodfellow et al, 2014;Grover et al, 2018;Theis et al, 2015;Zhao et al, 2020) and seen in our results: the RNN has a worse F = 28 hold-out likelihood than the polynomial, yet the polynomial model explodes unlike the RNN. In this case, the phenomenon of 'explosion' is not significantly penalising the likelihood.…”
Section: For Evaluationsupporting
confidence: 62%
“…Poor performance in certain aspects may be overshadowed by good performance elsewhere. This can result in cases where increased hold-out likelihoods do not always correspond to better sample quality, as noted in the ML literature (Goodfellow et al, 2014;Grover et al, 2018;Theis et al, 2015;Zhao et al, 2020). In our work, although the RNN has the greatest likelihood for F = 23, it does not have the smallest KL-divergence for the 1D histograms in Figure 7.…”
Section: Why Likelihood Is Usefulsupporting
confidence: 48%
“…The use of information theory to study and improve neural networks is a relatively new yet promising direction of research (Lee, Tran, & Cheung, 2021;Nowozin, Cseke, & Tomioka, 2016;Principe, 2010;Achille & Soatto, 2019;Chen et al, 2016;Wickstrom et al, 2019;Tishby & Zaslavsky, 2015;Alemi, Fischer, Dillon, & Murphy, 2017;Zhao, Cong, Dai, & Carin, 2020;Zaidi, Estella-Aguerri, & Shitz, 2020). While many GANs loss functions are based on the Jensen-Shannon divergence, there are other divergence measures and tools in information theory that can be directly applied to the design of GANs.…”
Section: Prior Workmentioning
confidence: 99%
“…The family of loss functions that simplify down to f -divergences was thoroughly studied in Nowozin et al (2016), Farnia & Tse (2018), and Li et al (2019). Bridging the gap between maximum likelihood learning and GANs, especially those with loss functions that simplify down to f -divergences, has also been analyzed in Zhao et al (2020). Using the symmetric Kullback-Leibler (KL) divergence, researchers have also shown that a variant of VAEs is connected to GANs (Chen et al, 2018).…”
Section: Prior Workmentioning
confidence: 99%